Programa psicoeducativo para potenciar los estilos de comunicación familiar, dirigido a padres y niños/as de sexto año paralelo “B”, de la escuela de educación básica Ing. José Alejandrino Velasco, 2013-2014 - Ojeda Moreira, María Gabriela (2014)
The research aimed to implement a psychoeducational program to enhance family communication styles aimed at parents and children / year as the sixth side "B" Basic Education School "Ing. Jose Alejandrino Velasco 2013-2014; descriptive cross-sectional study, quasi-experimental design with a sample of 34 boys / 32 girls and parents. In the process of research methods and procedures as scientific, analytic-synthetic, inductive, deductive, historical and logical were used. In addition to diagnosis, development and application of models and evaluation of the effectiveness of the alternative; the technique of structured questionnaire and scale of communication between parents and children Barnes and Olson used. Diagnostic Results: 75% of parents do not talk openly to their children; the pre-test and 58.80% had problems communicating with the father; 52.90% with the mother. The percentage of open communication is 73.53% with mother and father with 58.82%. The alternative proposal was validated through linear correlation method of Pearson r r (xy) = 0.72 high positive correlation. We conclude that the investigated in a high percentage reported having family communication problems. The proposed intervention achieved moderate to high positive correlation.